Malignant transformation in oral lichen planus and oral lichenoid lesions: A retrospective study / Low Yin Kuan - Low , Yin Kuan (2024)
Background: Oral lichen planus (OLP) and oral lichenoid lesions (OLLs) are chronic inflammatory diseases associated with T-cell mediated immunological dysfunction and are classified as oral potentially malignant disorders (OPMDs). Studies have provided evidence of malignant potential of OLP and OLL but studies targeting Asian population is lacking. There is inconsistency in the malignant transformation (MT) rate of OLP and OLL. Objectives: The aim of this study was to determine the MT rate of OLP and OLL diagnosed at the Oral Medicine Clinic, Faculty of Dentistry, Universiti Malaya. The specific objectives were to determine the prevalence of OLP/OLL diagnosed at the Diagnostic Oral Pathology Unit, Faculty of Dentistry, Universiti Malaya. This study also sought to determine the socio-demographic, clinical features, histopathological features and MT rate of OLP and OLL in patients seeking treatment at the Oral Medicine Clinic, Faculty of Dentistry, Universiti Malaya. Methods: A retrospective study was conducted by retrieving pathologic reports of OLP, OLL and oral epithelial dysplasia (OED) with a provisional diagnosis of OLP and OLL from the year 2008-2018. Clinical notes of the retrieved cases were reviewed to look for evidence of malignant transformation. Histopathological slides were reviewed to evaluate the histopathological features of OLP, OLL and OLP/OLL with dysplasia. Results: The prevalence of OLP/OLL was 5.7%. Most of the cases were OLL, followed by OLP and OLP/OLL with dysplasia. The overall MT rate for OLP was 1.89%. The specific MT rate for OLP, OLL and OLP/OLL with dysplasia was 0%, 0% and 12.5% respectively. The most common dysplastic features seen were premature keratinization in single cell and generalized premature keratinization. Conclusions: OLP/OLL with dysplasia showed the highest MT rate. It is important to regularly follow-up OLP and OLL patients, particularly those with dysplastic changes.